2014
DOI: 10.1186/s12862-014-0176-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenomics of the Old World monkey tribe Papionini

Abstract: BackgroundThe evolutionary history of the Old World monkey tribe Papionini comprising the genera Macaca, Mandrillus, Cercocebus, Lophocebus, Theropithecus, Rungwecebus and Papio is still matter of debate. Although the African Papionini (subtribe Papionina) are generally considered to be the sister lineage to the Asian Papionini (subtribe Macacina), previous studies based on morphological data, nuclear or mitochondrial sequences have shown contradictory phylogenetic relationships among and within both subtribes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 99 publications
6
52
0
1
Order By: Relevance
“…The general topology of our phylogenetic tree for Papio in eastern Africa is similar to those found in earlier studies (Zinner et al, 2009a(Zinner et al, , 2011Liedigk et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…The general topology of our phylogenetic tree for Papio in eastern Africa is similar to those found in earlier studies (Zinner et al, 2009a(Zinner et al, , 2011Liedigk et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…Since multiple outgroups improve phylogenetic results (e.g., Maddison et al, ; Strait and Grine, ), we additionally assigned Macaca as an outgroup. Macaca was chosen because it is universally recognized as the sister taxon to the other extant papionins (Cronin and Sarich, ; Szalay and Delson, ; Strasser and Delson, ; Disotell et al, ; Disotell, ; Harris and Disotell, ; Fleagle, ; Tosi et al, ; Harris, ; Xing et al, ; but see Liedigk et al, ). Rungwecebus was excluded as an outgroup due to the lack of any adult specimens (see Davenport et al, ; Gilbert et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In these studies, C. torquatus clustered with Mandrillus forming a sister group to other Cercocebus taxa, suggesting contemporary and/or ancient introgressive hybridization among these sympatric species. In the most recent study, Liedigk et al () found a single mitochondrial genome of C. chrysogaster to be closely related to Mandrillus leucophaeus . Thus, while uncertainty exists regarding the relationships within the genus Cercocebus , none of the previous biogeographic hypotheses proposed in the literature are well‐supported by recent molecular analyses.…”
mentioning
confidence: 99%
“…It is likely that TAAR8 was pseudogenized in Simiiformes but subsequently resurrected in humans (magenta). The tree is obtained from recent primate phylogenetic studies 47,48,84 and their approximate divergence times (MYA) are obtained from Perelman et al 47 Interestingly, all African apes (Homininae) have lost TAAR4. Two independent TAAR4 pseudogenization events in two arboreal primates, the white-cheeked gibbon and the marmoset, were also observed.…”
Section: Hylobatidaementioning
confidence: 99%